A functional dried fruit matrix incorporated with probiotic strains: Lactobacillus Plantarum and Lactobacillus Kefir - Rêgo, A. (2014)
The consumption of probiotic functional foods, i.e. processed foods enriched with microorganisms that confer health benefits to the host, shows a progressive increase in the last decade due to changes in habits and trends of consumers attracted by the benefits of these products. Currently, the development of fruits and vegetables with probiotic content is a topic of high interest for the probiotic-food consumers as these are a popular item perceived as healthy by consumers, and issues related with lactose intolerance are overcome. The aim of this research study was to develop a new healthy dry food that contains a source of probiotic strains providing some benefits to consumers. Apple was selected as an experimental food matrix and two different probiotic Lactobacillus species, L. plantarum and L. kefir, were tested separately. Samples were taken immediately before and after the drying process in order to determine the viability of bacteria adhered to the matrix. Dried apple cubes were stored in sterile closed glass containers or in sealed bags vacuum packed and normal atmosphere) at room temperature and at 4ºC. The bacterial viability in the dried product was tested at different storage times. For both probiotic strains, a decrease of approximately 2 log cycles in bacterial cell numbers was observed after drying. The bacterial number in apple cubes at the time of storage at room temperature and 4ºC was approximately 1x107 cfu/g. Both probiotic strains died after one month of storage at room temperature, while during storage at 4ºC the cells remained viable after 3 months, with bacterial number around 1x106 cfu/g.